Modeling of the Soil Structure Interaction Problem with 3D detailed modeling - El-Chouli, Rana; Suleiman, Farah (My University, 2015)
The research work presented in this thesis deals with the modeling of the soil-structure interaction (SSI) by accounting for material nonlinearities while foreseeing the discretization of the superstructure through the use of hybrid-models (HYMOD) and the soil domain through the use of hexahedral elements that incorporate an elasto-plastic material model. In order to parametrically investigate this modeling concept, a full-scale 5-storey reinforced concrete building that was seismically strengthened was modeled and analyzed for different load combinations. Three models were considered in order to investigate the overall and local effects of the SSI phenomenon on the mechanical response of the structure for different loading scenarios, where the derived crack patterns and the building’s foundation-soil interaction were investigated. The stress-strain development within the soil domain is also presented and discussed for both vertical linear static and horizontal nonlinear static loading conditions. The numerical investigation showed that the structure has met the seismic demands, and the raft slab which is used as the foundation system has helped minimizing any adverse effect of the SSI. Furthermore, the proposed modeling provided an in-depth analysis of the SSI problem in relation to the overall mechanical behavior of the RC structure. Finally, it was concluded that nonlinear modeling for ultimate limit-state loading conditions of SSI systems through the use HYMOD is computationally feasible; while the computational cost should be further reduced through the integration of ReConAn FEA with parallel solvers.
Keywords: Seismic Assessment; Soil Structure Interaction; Reinforced Concrete; Nonlinear Analysis; Hybrid Modeling; 3D Detailed Modeling